Tf2O‐Mediated Regioselective C(sp2)−H Sulfenylation of Enaminones Using Methyl Sulfoxides as Sulfur Sources. Issue 4 (11th March 2022) - Zhang, Changyuan; Luo, Jian; Zhang, Jiantao; Chen, Lulu; Zhu, Xuncheng; Guo, Mengping; Shen, Chan; Li, Zeng; Wang, Wei
Abstract: An efficient Tf2 O‐mediated regioselective C(sp 2 )−H sulfenylation of enaminones has been described. Methyl sulfoxides are employed as sulfur sources to react with different types of enaminones under mild reaction conditions, providing a straightforward approach for the synthesis of β‐amino sulfides in up to 97% yield via one‐pot manner. Moreover, this sulfenylation proceeded smoothly with oxidant‐free and metal‐free. Abstract : An efficient Tf2 O‐mediated regioselective C(sp 2 )−H sulfenylation of enaminones has been described. Methyl sulfoxides are employed as sulfur sources to react with different types of enaminones under mild reaction conditions, providing a straightforward approach for the synthesis of β‐amino sulfides in up to 97% yield via one‐pot manner. Moreover, this sulfenylation proceeded smoothly with oxidant‐free and metal‐free.